SOIL COMPACTION AND ITS IMPACT ON SOIL PROPERTIES, MICROBIOME, GREENHOUSE GAS EMISSION AND PLANT ROOT GROWTH - Poonam Bhatt; Prashant Raj Giri; Balchisu Napari (Big Data in Agriculture)
Soil compaction, a significant agricultural issue due to heavy machinery uses and pressures for frequent tramplings, alters soil properties, leading to erosion, nutrient depletion, and pollution. Factors such as soil water content, bulk density, and texture determine soil susceptibility to compaction. This review paper addresses the knowledge gap on the impact of compaction on soil functioning, crop yield, and the environment, focusing on the soil microbiome, greenhouse gas emissions, and carbon storage. Root penetration is crucial for plant growth, but compacted soil limits water and nutrient access, reducing yields. Soil compaction management strategies include restricted traffic patterns, organic matter addition, and using plants like alfalfa to break compacted zones and promote macropore formation. Earthworm activity and proper crop management also help mitigate compaction effects. Soil compaction jeopardizes the soil microbiome’s role in nutrient cycling and plant productivity, disrupting soil fertility, carbon storage, and greenhouse gas emissions. It also hinders soil carbon sequestration, impairing the potential carbon sink and contributing to increased atmospheric greenhouse gases. This comprehensive review paper contributes valuable insights for designing sustainable agricultural practices prioritizing soil health, ecosystem resilience, and food security.